Equity pricing, volatility and skewness : the dynamic behaviour and interactions of first and second moments in the Euro area and United States stock markets - Poti, Valerio (Trinity College (Dublin, Ireland). Trinity Business School, 2006)
This thesis contributes to the empirical asset pricing literature on both the cross- section and time series of stock returns. It also contributes to the recent but rapidly growing literature on total and idiosyncratic risk and to the literature on the dependence structure of stock market returns. Concerning the asset pricing problem, the main contribution is a novel beta-pricing representation of Harvey and Siddique’s (2000) 3-moment conditional CAPM. Its main advantage is that both its beta coefficients and risk premia can be interpreted as parameters of appropriate regression models. In an empirical application to US stocks sorted into 30 industry portfolios, I add to the extant evidence that, while coskewness helps explain a substantial portion of the cross section of average returns and the coskewness premium is of the same order of magnitude as the covariance premium, the estimated unconstrained 3-moment model implies a utility function that is not concave over the relevant wealth range.
Keywords: Business Studies, Ph.D.; Ph.D. Trinity College Dublin